The timing of vision in basketball three-point shots - Piras, Alessandro (Frontiers in Psychology, 2024)
The aim of the present study was to explore the relationship between gaze behaviour, motor responses and the direction of visual attention when different levels of basketball players were engaged in a basketball three-point shot. Twelve near-experts and 12 amateur basketball players, wearing an eye tracker and an inertial sensor, performed 20 shots on a basketball field, receiving the ball from a teammate, who then acted as the opponent. The trial sequence was subdivided into catching, aiming and ball flight phases. The analysis demonstrated that near-experts exhibited longer fixation durations and saccades of lower amplitude and peak velocity than amateurs. The gaze behaviour showed that all players utilized fixations during the last part of the catching phase, during most of the aiming phase, and during the final part of the ball flight phase. The greatest number of saccades was exhibited between the aiming and the ball flight phases, when the ball was released by the players. Saccades were oriented toward the teammate during the catching phase. Instead, during the aiming and ball flight phases, saccade orientations were not polarized toward a specific visual cue. In conclusion, vision plays a critical role in every aspect of the three-point shot in basketball, from catching the ball, to aiming preparation, and shot execution. It is a key factor in decision-making, spatial awareness, and overall performance in team sports.